Implementation of the project to strengthen the profile of pancasila students (p5) based on local wisdom in primary schools - Sumarni, Margaretha; Jewarut, Siprianus; Kusnanto, Kusnanto; Melati, Felisitas Victoria (Jurnal Bidang Pendidikan Dasar, 2024)
The Pancasila student profile has six basic principles which refer to Pancasila values. One of the themes implemented for the project to strengthen the Pancasila student profile is the theme of local wisdom, where the implementation aims to enable students to increase and develop potential based on local wisdom values ​​to support their achievement. Pancasila Student Profile. The method used in this research process is descriptive qualitative with stages of observation methods in schools, conducting interviews with homeroom teachers and school principals, as well as documentation to fulfil data completeness. The data instruments are a list of questions on the questionnaire and interview sheet. With this research, it is hoped that schools can implement projects to strengthen the profile of Pancasila students to the maximum.